2019
DOI: 10.3390/biom9040126
|View full text |Cite
|
Sign up to set email alerts
|

Greensporone A, a Fungal Secondary Metabolite Suppressed Constitutively Activated AKT via ROS Generation and Induced Apoptosis in Leukemic Cell Lines

Abstract: Greensporone A is a fungal secondary metabolite that has exhibited potential in vitro for anti-proliferative activity in vitro. We studied the anticancer activity of greensporone A in a panel of leukemic cell lines. Greensporone A-mediated inhibition of proliferation is found to be associated with the induction of apoptotic cell death. Greensporone A treatment of leukemic cells causes inactivation of constitutively activated AKT and its downstream targets, including members GSK3 and FOXO1, and causes downregul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 55 publications
1
12
0
Order By: Relevance
“…During the dose selection of AKTi-1/2, only observation of cell death at the corresponding doses was used in the methodology, which is a limitation of the present study. A previous study found that AKTi-1/2 can induce cell apoptosis by downregulating Mcl-1 expression in leukemic cells ( 34 ). Therefore, the mechanism by which isoliensinine induces apoptosis in cervical cancer cells may be similar to that by AKTi-1/2.…”
Section: Discussionmentioning
confidence: 99%
“…During the dose selection of AKTi-1/2, only observation of cell death at the corresponding doses was used in the methodology, which is a limitation of the present study. A previous study found that AKTi-1/2 can induce cell apoptosis by downregulating Mcl-1 expression in leukemic cells ( 34 ). Therefore, the mechanism by which isoliensinine induces apoptosis in cervical cancer cells may be similar to that by AKTi-1/2.…”
Section: Discussionmentioning
confidence: 99%
“…(strain S1a1) was isolated. A chemical study of the ethyl acetate extract of a solid rice medium culture yielded three new [penitanzchroman (114) and tanzawaic acids Y (115) and Z (116)] and six known tanzawaic acid derivatives [arohynapene A (117) and tanzawaic acids A (118), B (119), E (120), M (121), and N (122)], three isochromans [(3S)-6-hydroxy-8-methoxy-3,5dimethylisochroman (123), (3S,4R)-6-hydroxy-8-methoxy-3,5-dimethylisochromanol (124), and (1S,3S)-1,6-dihydroxy-3,5-dimethyl-8-methoxyisochroman (125)], and two benzoquinones [anserinones A (126) and B (127)]. 139 Furthermore, investigation of the same fungus using the OSMAC (one-strain many-compounds) approach 140 afforded tanzawaic acid Z1 (128).…”
Section: Journal Of Natural Productsmentioning
confidence: 99%
“…While preparing this manuscript, the total synthesis of compounds 21 and 22 was achieved and the absolute configuration of the stereogenic centers of the tetrahydrofuran rings was established as (5 R ,8 R ) . In a set of pharmacological evaluations, greensporones A ( 10 ) and C ( 14 ) were found to suppress the growth of leukemic cells via induction of apoptotic cell death. , An additional point about this particular example is that there was nothing remarkable about the collection of the fungus. Members of our team were simply demonstrating collecting techniques to a group of students, and yet, a species was isolated that yielded a suite of 14 new resorcylic acid lactones.…”
Section: Part Ii: Chemical Diversity Of Freshwater Fungimentioning
confidence: 99%
“…Washed the obtained pellet with PBS and centrifuged for 3 min. A last, of PBS (400 µL) was added and analyzed by flow cytometer (BD Biosciences, San Jose, CA, USA) [43].…”
Section: Measurement Of Ros By Flow Cytometrymentioning
confidence: 99%